Point Absorber with Direct-Drive Power Take-Off System for Low Wave Application - Ishak, A.M. (Institute of Electrical and Electronics Engineers Inc., 2021)
A direct-drive system with a permanent magnet linear generator has been an attractive solution for wave energy converter devices. Exploiting the reciprocating movement of wave motion has enabled the application of linear generators to wave energy converter devices. This paper presents the computational simulation of the Permanent Magnet Linear Generator design for a point absorber wave energy converter. The electromagnetic analysis was done using the Finite Element Analysis software, ANSYS. With this analysis, results on the flux distribution, air gap flux density and open-circuit results of the proposed design were gathered. A lab-scale device was constructed to validate a simple version of a single-phase linear generator design. A comparative study of both simulation and experimental results of the linear generator was carried out. Based on the results, the percentage error between simulation and experimental obtained was acceptable. To maximize power generation, an improved version of the linear generator based on an actual ocean profile was proposed. Â© 2021 IEEE.